Facts and Faction: The Development of Church and State Relations in Democratic South Africa from 1994–2012 - Simangaliso Kumalo, Raymond (A journal of church and state, 2014)
When the constitution of democratic South Africa was adopted, it had a clause that signified a major shift for the country from being a Christian state to a rel